Active community inquiry facing COVID-19: Experiences in the Cumanayagua municipality, 2020 - Victor René Navarro Machado; Blanca Moracén Rubio; Danays Santana Rodríguez; Oskeymi Rodríguez González; Medelyn Oliva Santana; Guiguiola Blanco González (Medisur)
Foundation: active research is a tool that facilitates the detection of relevant diseases in the epidemiological profile. Objective: to describe the experiences in the implementation of a municipal community active research system for COVID-19. Methods: prospective, descriptive, cross-sectional study carried out in the municipality of Cumanayagua, Cienfuegos province, Cuba, between March 19 and April 17, 2020. The universe was all the inhabitants (48,412) and researchers ( 627) in that period. Medical records, municipal statistics were reviewed and participatory observation was used. Results: active research structure, its basis from the family doctor-nurse's office and its form are described by interviewing the residents in their homes. A total of 627 researchers, mainly health professionals (43.38%) and medical students (33.33%), evaluated daily up to 88.88% of all residents and 95.28% of all homes dispensed in the territory. The research system allowed detecting 97, 08% of the acute respiratory infections diagnosed in the municipality. Conclusions: massive community active research carried out by the basic health team, medical sciences students and professionals from various sectors, has allowed: access to all the communities, daily research of the majority of the inhabitants and respiratory infection accuracy incidence in the municipality. The implemented system was properly articulated to the family physician-nurse program at the primary care level.